DETERMINING THE PREFERENCES OF A SOCIAL GROUP STATISTICALLY AND DYNAMICALLY - Kamal Taha (European Scientific Journal, ESJ, 2014)
In this paper, we propose a group-based Collaborative Filtering framework. The framework uses ontology-driven social networks, where nodes represent social groups. A social group is an entity that defines a group based on demographic, ethnic, cultural, religious, age, or other characteristics. In the proposed framework, query results are filtered and ranked based on the preferences of the social groups to which the user belongs. If the user belongs to social group Gx, results will be filtered based on the preferences of Gx. The framework can be used for various practical applications, such as Internet or other businesses that market preference-driven products. In the proposed framework, the preferences of a Social Group can be acquired statically from hard-copy published studies about the Social Group or can be acquired dynamically from Web pages that publish information about the Social Group. We describe and experimentally compare the above mentioned approaches.